The relative age effect among female basketball players in the Israeli Premier League - Avugos, S.; Malul, M. (Frontiers in Sports and Active Living, 2025)
In sports, the term relative age effect refers to the asymmetrical distribution of athletes based on their birth dates relative to an arbitrary cut-off date. Some studies indicate that athletes who were born shortly after this cut-off tend to have higher representation in elite sports leagues compared to those who were born later in the year. Yet the literature presents inconsistencies in empirical support for this effect. The aim of this study, therefore, was to examine the relative age effect in female basketball players from the Israeli Premier League, while distinguishing between domestic and foreign players (n = 215, M age = 24.08 years, SD = 5.17; and n = 120, M age = 30.33 years, SD = 3.68, respectively), and examining two alternative cut-off dates (January 1 and September 1). Data were collected over six seasons, 2018-2024. Chi-square values and odds ratios were calculated to examine the distribution of birth quarters compared to uniform distribution in general, and to Israeli and U.S. live birth data. The findings reveal that the relative age effect was insignificant among the players, regardless of their nationality. While a higher number of players were found to have been born in the second quarter of the year, this difference was statistically insignificant, regardless of whether a uniform distribution of births or normative population values were applied. As such, the findings of the current study do not support the existence of selection bias among coaches based on the birth dates of female professional basketball players in Israel.